Mewaspadai Pembajakan Operasi Perdamaian: Telaah Kritis Intervensi Asing dalam Konflik Libya - Nuruddin Al Akbar (Global South Review, 2015)
This study seeks to explore the hidden challenges to the mission/operation of peace (peace operation/mission). Ideally, as envisioned by the perspective of liberal peace, humanitarian mission should be carried out purely on the basis of values of humanism in order to address the humanitarian crisis phenomenon. However, this assumption has weaknesses because it is ignorant of potential piracy against peace operations in which the latter are just cover for the implementation of the vested interests of the actors involved in the mission. Piracy against peace operations is essentially a new form of "civilizing mission", the strategy used by colonialist countries in order to give legitimacy to their rule in the colonies. The essence of the "civilizing mission" strategy is to show the invaders as a helper of the colonized countries. This study would like to explore how piracy against these peace operations occur in the context of Libya (2011). A number of foreign countries such as the United States are involved in peace operations in Libya, with the primary mission to implement a no-fly zone and protection of human security. This study includes a discussion of the vested interests behind the peace mission, the discourse used by the actors mission to wrap their vested interests as purely based on humanism, and the impact of of this strategy to the conduct of peace operations in general.